2018
DOI: 10.1557/mrc.2018.215
|View full text |Cite
|
Sign up to set email alerts
|

Developing a novel continuum model of static and dynamic contact angles in a case study of a water droplet on micro-patterned hybrid substrates

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…On the one hand, the roughness and geometry of the microchannel have a certain impact on the liquid flow, for example, Kasiteropoulou et al [6] used numerical methods to deeply study the impact of wall roughness on the fluid flow and found that near the rough wall, the fluid particles tend to be trapped in the wall cavity, and the flow rate will decrease with the narrowing of the channel. Arash et al [7] also used numerical methods to study how a water droplet interacts with micrometer-sized patterns of a hybrid hydro-phobic/-philic surface and revealed the details of the droplet-surface interaction. On the other hand, the hydrophilicity of microchannels also affects the flow of liquid, especially when capillary force is dominant.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the roughness and geometry of the microchannel have a certain impact on the liquid flow, for example, Kasiteropoulou et al [6] used numerical methods to deeply study the impact of wall roughness on the fluid flow and found that near the rough wall, the fluid particles tend to be trapped in the wall cavity, and the flow rate will decrease with the narrowing of the channel. Arash et al [7] also used numerical methods to study how a water droplet interacts with micrometer-sized patterns of a hybrid hydro-phobic/-philic surface and revealed the details of the droplet-surface interaction. On the other hand, the hydrophilicity of microchannels also affects the flow of liquid, especially when capillary force is dominant.…”
Section: Introductionmentioning
confidence: 99%